Che cosa è l’identità collettiva? Denotazioni empiriche e/o ipotesi di ipostatizzazione del concetto - Daher, Liana M. (SocietàMutamentoPolitica, 2013)
The analysis of the concept of identity becomes significantly more complicated as regards both the global and multicultural contemporary society and collective subjects, the boundaries of which are not clear. Therefore, denotation and empirical gathering appear to be complex and require careful reflection before the field research is carried out, opening up epistemological and theoretical questions and considerations.